Trigonmetric integral

Calculus Level 3

1 3 1 π cos ( 2 π 3 x ) + π cos ( π 3 x ) 2 sin ( π 2 x ) sin ( 2 π 3 x ) + 2 sin ( π 2 x ) sin ( π 3 x ) d x \int_{\frac{1}{3}}^{1} \frac{\pi \cos(\frac{2\pi}{3}x) + \pi \cos(\frac{\pi}{3}x) }{ 2\sin(\frac{\pi}{2}x)\sin(\frac{2\pi}{3}x) + 2\sin(\frac{\pi}{2}x)\sin(\frac{\pi}{3}x)} dx

If the value of the definite integral above is A A , find 9 A 2 9A^{2} ?


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

After simplification the integrand becomes π 2 cosec π x 2 cot π x 2 \dfrac{π}{2}\cosec \dfrac{πx}{2}\cot \dfrac{πx}{2} . Substituting y y for π x 2 \dfrac{πx}{2} , we get the value of the integral as cosec π 6 cosec π 2 = 2 1 = 1 \cosec \dfrac{π}{6}-\cosec \dfrac{π}{2}=2-1=1 . Hence A = 1 A=1 and 9 A 2 = 9 9A^2=\boxed 9 .

Albaraa Alsharif
Feb 19, 2020

By taking out the common factors, we get :

1 3 1 π [ cos ( 2 π 3 x ) + cos ( π 3 x ) ] 2 sin ( π 2 x ) [ sin ( 2 π 3 x ) + sin ( π 3 x ) ] d x \int_{\frac{1}{3}}^{1} \frac{\pi [ \cos(\frac{2\pi}{3}x) + \cos(\frac{\pi}{3}x) ]}{2\sin(\frac{\pi}{2}x) [ \sin(\frac{2\pi}{3}x) + \sin(\frac{\pi}{3}x) ]} dx

Now, the integrand can be factorized using these trigonometric identities :

sin ( α ) + sin ( β ) = 2 sin ( α + β 2 ) cos ( α β 2 ) \sin(\alpha) + \sin(\beta) = 2\sin(\frac{\alpha + \beta}{2})\cos(\frac{\alpha - \beta}{2})

cos ( α ) + cos ( β ) = 2 cos ( α + β 2 ) cos ( α β 2 ) \cos(\alpha) + \cos(\beta) = 2\cos(\frac{\alpha + \beta}{2})\cos(\frac{\alpha - \beta}{2})

such that: α : 2 π 3 x , β : π 3 x α β 2 = π 6 x , α + β 2 = π 2 x \alpha : \frac{2\pi}{3}x , \beta : \frac{\pi}{3}x \rightarrow \frac{\alpha - \beta}{2} = \frac{\pi}{6}x , \frac{\alpha + \beta}{2} = \frac{\pi}{2}x

So...

1 3 1 π [ 2 cos ( π 2 x ) cos ( π 6 x ) ] 2 sin ( π 2 x ) [ 2 sin ( π 2 x ) cos ( π 6 x ) ] d x \int_{\frac{1}{3}}^{1} \frac{\pi [ 2\cos(\frac{\pi}{2}x )\cos( \frac{\pi}{6}x)\ ]}{2\sin(\frac{\pi}{2}x) [ 2\sin(\frac{\pi}{2}x) \cos( \frac{\pi}{6}x) ]} dx

After simplification :

1 3 1 π cos ( π 2 x ) 2 sin 2 ( π 2 x ) d x \int_{\frac{1}{3}}^{1} \frac{\pi\cos(\frac{\pi}{2}x )}{2\sin^2(\frac{\pi}{2}x) } dx 1 3 1 π 2 cot ( π 2 x ) csc ( π 2 x ) d x \rightarrow \int_{\frac{1}{3}}^{1} \frac{\pi}{2} \cot(\frac{\pi}{2}x) \csc(\frac{\pi}{2}x) dx

u-substitution:

u= π 2 x \frac{\pi}{2} x

du= π 2 d x \frac{\pi}{2} dx

π 6 x π 2 cot ( u ) csc ( u ) d u = csc ( π 2 ) [ csc ( π 6 ) ] = 1 \int_{\frac{\pi}{6} x}^{\frac{\pi}{2}} \cot(u) \csc(u) du = -\csc(\frac{\pi}{2}) - [-\csc(\frac{\pi}{6})] = 1

9 A 2 9 9A^2 \rightarrow \boxed{9}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...